Petty Justice : Low Law and the Sessions System in Charlotte County, New Brunswick, 1785-1867 - Craven, Paul, 1950- (Book collections on Project MUSE., 2014)
Petty Justice examines the role of justices of the peace and other front-line low law officials like customs officers and deputy land surveyors in colonial local government.